METHOD OF MEMORIZING AL-QUR’AN FOR LANSIA IN THE ISTIQOMAH TAKLIM ASSEMBLY GIWANGAN UMBULHARJO, YOGYAKARTA CITY - K Kafindi; Bambang Sumardjoko; Taufik Kasturi; Meti Fatimah (Universitas Muhammadiyah Surakarta, 2021)
This study aims to find out why the elderly are interested in memorizing the Al-Qur'an. This research uses a qualitative approach. The form of this research is a case study, a case study is a form of study that is very suitable for studying an event or situation in more depth, And to get a more comprehensive understanding of individual aspects, events, or situations and the focus of the study is the elderly who memorize Al-Qur’an in the Istiqomah Giwangan Umbulharjo Taklim Council, Yogyakarta City. The data were collected using the methods of documentation, observation and interviews. The results of this study indicate that the elderly are interested in memorizing the Al-Qur'an because they want to learn more about the Qur'an by memorizing. In this study, it was also found that age did not prevent them from memorizing the Qur'an. A strong desire for the elderly to memorize the Al-Qur'an is that they want to gain many benefits because as a basis for religion, reach for glory, And carry out obligations, all based on motivation to worship God. Meanwhile, the method used by the elderly in memorizing Al-Qur'an uses the Wahdah method.